ACEH AND IRAN BUSINESS COMMUNICATION BUILD - Azman; Salahuddin, Afriza; Nurdin, Hanifah (AT-TANZIR: JURNAL ILMIAH PRODI KOMUNIKASI PENYIARAN ISLAM, 2023)
The natural resources in Aceh is flooded, nonetheless, the local government of Aceh management, utilization and effort still not yet maximized. The agriculture, farming and husbandry, fishery, services and air transportations in Aceh could be handled and managed maximally. The land area of Aceh which is reached 2.3 hectares can be utilized for multipurpose. Additionally, the Islamic Laws products in Aceh are doubtful as well, particularly in cosmetics and food industry sectors. And the other hand, Islamic Republic of Iran which is considered as one of most strategic country in the world could be a solution for Aceh because of; Aceh needs to some of petrochemical and oil derivative products to support the constructions and infrastructure sectors and the other side Iran could be as a west Asia’s gate to distribute some of strategic commodities from Aceh such as CPO and paper and certainly in education sector Iran seemly could be beneficial for Acehnese students. The theory that used in this article was based on business communication and Para diplomacy concept. The result shown that are a lot of sectors that are potentially recognized as the strips of cooperation between Aceh and Islamic Republic of Iran. The collaborations between Iranian outstanding technology and Aceh natural resources will be tremendous way to reach the mutual objectives of both sides.